2005
DOI: 10.1002/macp.200400395
|View full text |Cite
|
Sign up to set email alerts
|

Study of the Degradation of an Epoxy/Amine Resin, 1

Abstract: Summary: The degradation of an epoxy/amine resin was studied under photolytic conditions in absence and in presence of oxygen and under thermooxidative conditions. The resin is obtained after curing the diglycidyl ether of bisphenol‐A (DGEBA) with a poly(propylene glycol) which is diamine terminated. The mechanisms of degradation of the two separate components before curing were also investigated. Analysis by IR and UV‐Vis spectroscopies revealed that the oxidation photoproducts detected during the degradation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
104
0

Year Published

2006
2006
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 142 publications
(107 citation statements)
references
References 15 publications
3
104
0
Order By: Relevance
“…Rivaton et al state that the observed profile has to be mainly attributed to limited oxygen diffusion, but also partly to absorption by photoproducts. Similarly, Mailhot et al 52,53 have found a photooxidation profile that reaches 300 lm into an epoxy-amine coating. In this case the cured resin had a glass transition temperature of only À50°C.…”
Section: Analysis Of Rate Phenomena Potentially Influencing the Oxidamentioning
confidence: 83%
See 2 more Smart Citations
“…Rivaton et al state that the observed profile has to be mainly attributed to limited oxygen diffusion, but also partly to absorption by photoproducts. Similarly, Mailhot et al 52,53 have found a photooxidation profile that reaches 300 lm into an epoxy-amine coating. In this case the cured resin had a glass transition temperature of only À50°C.…”
Section: Analysis Of Rate Phenomena Potentially Influencing the Oxidamentioning
confidence: 83%
“…The relationship between the dimensionless concentration of elastically effective network chains (y CC ) and the loss of benzene rings is unknown, but it seems possible that a 40% decrease in the crosslink density at the surface can lead to a reduction of 80% in the benzene concentration in the surface layer. For soft epoxy systems, Mailhot et al 53 have found an almost complete loss of aromatic character in the surface layer. In Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The growth of the polar groups can reduce the S parameter in large scale. On the other hand, UV irradiation induces chain scission reactions on coating surface, resulting in the formation of hydroxyl radicals [17]. Residual radicals, which are not consumed by oxygen in air, will reduce the formation of Ps, then contributing to a lower S parameter.…”
Section: S Parameter Analysismentioning
confidence: 99%
“…The silane coupling treatment can establish chemical bonding between the fiberglass of the FRC post and the core build-up materials. Plasma and UV irradiation are considered to clean surfaces by removing the organic contamination 11,15,16) , increasing the surface microroughness [16][17][18][19] , and changing the molecular structure of the surface area [16][17][18][19][20] . If the molecular structure of the matrix resin is changed, it is possible to create IPN bonding despite the thermoplastic polymers.…”
Section: Introductionmentioning
confidence: 99%